Characteristic feature of muslim exegesis - Ishakzadeh, M. (Journal of Oriental Studies, 2016)
The present article considres the characteristic feature of Muslim Exegesis, methods, types and styles of commentary of Koranic text. Special attention was given to genesis, chronology, history and structure of Muslim Exegesis tradition. The paper also contains the discussion about such essential problems of arrangement and organization of esoteric interpretation of Holy Koran.